Investigating Interpersonal Dynamics among Researchers and Innovators: An Ethnographic Study of Communication's Role in Fostering Innovation - Maryani, Anne; Triwardhani, Ike Junita; Yulianti, Y (KnE Social Sciences, 2024)
University plays an important role in innovation because of their role as producers of knowledge. Through researchers, the innovation ecosystem can develop and contribute to the progress of society. Complex innovation processes involve developing innovation systems that adapt to the uncertainty inherent in innovation. These networks, formed by researchers during the innovation process, encourage the continuous evolution of innovative ideas. The purpose of this research was: 1) Mapping the main problems of researcher concern to developing innovation. 2) Develop an institutional communication model to form a researcher ecosystem that develops high scientific impact. This research method is qualitative with an ethnographic communication approach. Informants are lecturers who are active in conducting innovative research and who are related to the scope of research activities in the institution. Data collection techniques were carried out using interviews, observations, and literature. Data processing was carried out by testing the validity of the data by triangulation through credible sources and references. Research findings were as follows: 1) Effective interpersonal communication drives researcher-stakeholder interaction in innovation. 2) The development of society is based on effective communication, which is formed by the mastery of science and technology. Scientists steer progress and growth by using communication tactics. Keywords: innovation, communication model, researcher, interpersonal communication, actor